Effect of season, needle age and elevated CO2 concentration on photosynthesis and Rubisco acclimation in Picea abies - Urban, Otmar; Hrstka, Miroslav; Zitová, Martina; Holišová, Petra; Sprtová, Mirka; Klem, Karel; Calfapietra, Carlo; De Angelis, Paolo; Marek, Michal V (Plant physiology and biochemistry, 2012)
While downward photosynthetic acclimation in response to elevated CO(2) (EC) is frequently accompanied by reduction in Rubisco (ribulose-1,5-bisphosphate carboxylase/oxygenase), the exact mechanism behind this decrease and its dynamics are not well understood. We comprehensively studied Rubisco adjustment to EC in coniferous Picea abies using an electrophoretic (protein content), spectrophotometric (initial (RA(initial)) and total (RA(total)) in vitro Rubisco activities), and gas-exchange (maximum carboxylation activity in vivo (V(Cmax))) techniques. With respect to differing carbon sink strength and nitrogen remobilization, we hypothesized greater acclimation of photosynthesis in one-year-old as compared to current-year needles and at the end than at the beginning of the vegetation season. EC treatment led to a decrease in V(Cmax) values in current-year needles, but the ribulose-1,5-bisphosphate (RuBP)-limited rate of photosynthesis (J(max)) remained unaffected. Indeed, both V(Cmax) and J(max) were reduced by the EC treatment in one-year-old needles. The extent of photosynthetic acclimation in EC plants did not increase, however, during the vegetation season. EC decreased the activation state of Rubisco (RA(initial)/RA(total)) by 16% and 5% in current-year and one-year-old needles, respectively (averaged over the growing season). While during spring (short-term effect) EC treatment did not influence the Rubisco content per unit leaf area and decreased its specific activity (activity per unit Rubisco mass) in both needle age classes studied, exposure to EC during the entire vegetation season tended to reduce the Rubisco content while increasing its specific activity. Irrespective of CO(2) treatment and needle age, a hyperbolic-decay relationship was observed between Rubisco-specific activity and its content.
Keywords: Photosynthesis; Plant Leaves; oxid uhličitý; aklimatizace; ribulosa-1,5-bisfosfát-karboxylasa; Carbon; roční období; Carbon Dioxide; Picea; smrk; uhlík; Acclimatization; fotosyntéza; Nitrogen; dusík; Ribulose-Bisphosphate Carboxylase; Seasons; listy rostlin